Performance Insights on the National Evaluation in Romania - Octavian CEBAN; Ionela-Roxana PETCU; Andreea MIRICĂ; Marian NECULA; Roxana-Violeta PARTAS-CIOLAN; Liliana CATRINA (Communications of International Proceedings, 2021)
The paper explores the statistical association between sex and area of residency vs absenteeism and performance on the Romanian National Evaluation, a mandatory national examination required for completing the primary education cycle. While a plethora of similar studies regarding children access rate in primary education focus on the determinant drivers such a demographics, income and other spatial correlated variables, there is a research gap on statistical models used to assess attendance and performance in the National Evaluation and demographic factors. We employ a chi-squared test and a logistic regression model to test the statistical hypotheses of association, and while there is a significant association between sex/area of residency and absenteeism/performance on the Romanian National Evaluation in terms of chi-squared statistics, the logistic model fails to detect any statistically significant relation in terms of probability.
Keywords: Secondary Education; Examination Performance; Examination Absenteeism.